TRANSNATIONALE VIRTUELLE TEAMKOLLABORATION Die Auswirkung der Einführung von Microsoft Teams auf die Teamkollaboration am Beispiel des Globalvorhabens "Bodenschutz und Bodenrehabilitierung für Ernährungssicherung" - Pracht, Sarah Antonia (Jihočeská univerzita, 2021)
This master thesis examines transnational virtual team collaboration using the example of the global programme "Soil protection and rehabilitation for food security" implemented by the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ). Using the virtual collaborative team spread across 8 countries, the impact of the introduction of Microsoft Teams, a collaboration software, was studied. Qualitative guided interviews were used to collect data that provided information on various aspects of transnational team collaboration such as communication, trust, identification, or satisfaction. Subsequently, a qualitative content analysis was used to evaluate the data, which led to the conclusion that Microsoft Teams improved transnational collaboration in many respects according to the interviewees' perceptions. Nevertheless, aspects that could be improved in the context of transnational virtual collaboration with MS Teams in the global programme were also identified.
TRANSNATIONAL VIRTUAL TEAM COLLABORATION The impact of the introduction of Microsoft Teams on team collaboration using the example of the global program "Soil Protection and Rehabilitation for Food Security"
Keywords: team collaboration; virtual teams; transnational teamwork; multicultural teams; Information and communication media; Microsoft Teams; team trust; work motivation; team identification; team cohesion; job satisfaction; team collaboration; virtual teams; transnational teamwork; multicultural teams; Information and communication media; Microsoft Teams; team trust; work motivation; team identification; team cohesion; job satisfaction